KEBIJAKAN PENGELOLAAN TARIF PELABUHAN TERMINAL KHUSUS PT. PERTAMINA (PERSERO) REFINARY UNIT II DUMAI (STUDI IMPLEMENTASI KEPUTUSAN MENTERI PERHUBUNGAN NO. 54 TAHUN 2002) - Asthari Novianti; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This essay is a result of research conducted on a special port Pertamina Dumai City formulation of the problem 1) How implementation of management policies port tariffs special terminal PT. Pertamina (Persero) Refinary Unit II Dumai? 2) factors that influence the success of a particular terminal port management policy PT.Pertamina (Persero)? 3) What factors are causing non-performance of KM No. 54 Tahun 2002 tentang pembagian hasil jasa labuh that should be submitted to the Government Dumai as tax state revenue (non-tax)? The research method is descriptive method with qualitative research approach. Interview data collection techniques, documentation and technical literature. Informant in this research is the Head of Department of Transportation in Dumai, Head of Sea Transportation, Section Head harbor, Member of Commission II DPRD Kota Dumai and Section 5 of port staff Transportation Agency Dumai. Types and Sources of Data 1) Primary Data is data obtained directly from the respondents in the field over which the authors ask questions through certain methods related to the problems examined. 2) Secondary Data, the data obtained through documents, books, records and other documentation which are above explanation of the problem being investigated. Results of the research are: 1) Keputusan Menteri Perhubungan No. 54 Tahun 2002 tentang penyelenggaraan pelabuhan at first PT. Pertamina did not want to provide services moored vessels using the harbor to the Government Dumai given Decree of the Minister of Communications No. 88/0/1972 and SKB relationship between the Director General of Sea and CEO of Pertamina, given the absence of repeal and replacement of the top two. Pertamina added that according to the Keputusan Menteri Perhubungan No. 54 Tahun 2002 on Chapter XV Final Provisions Article 63 stated despite the Minister's decision is enforced, but legislation that level or lower than the Ministry of Transportation, which regulates the operation of sea port, shall remain valid as long as not contrary to or not been replaced with new ones. 2) In the course wajtu, sharing services and anchor from the Special Port or Place For Your Own Interests (DUKS) has been divided proportionally by 30% by the Government Pertamina Dumai, this after the signing of the Memorandum of Understanding (MoU) which continued signatories Agreement Technical Labuh Payment Services in the Port PT. Pertamina Dumai on December 3, 2009 at the Hotel Grand Zuri in Jakarta, who signed the MoU PT. Pertamina Dumai City Government and PT. Pelindo. The income is income Dumai City Government, which will be realized to the majority of people in Dumai, to support development in all fields that can improve the welfare of the community. Keywords: Implementation, Policy